Learning Quality, Time Management and Social Support on Student Academic Achievement - Aliffany Pualam Ariarta; Mohammad Lutfi Alil Mu'in; Muhammad Sabri Latif; Azrina Hilmi Saadah; Sri Harini (LP. Ma'arif Janggan Magetan, 2024)
This study aims to determine the effect of learning quality, time management and social support on the academic achievement of postgraduate students of UIN Maulana Malik Ibrahim Malang. The method used in analysing research data is descriptive quantitative with a sample of 80 students. The sampling technique used is Non Probability Sampling technique. The results showed the Wald test results with a significance value of learning quality of 0.000 and social support of 0.021 smaller than the value of the error rate of 0.05. While time management with a significance value of 0.348 is greater than the error rate value of 0.05, meaning that time management has no correlation and has no significant effect on student academic achievement. The odds ratio value of learning quality (X1) is 18.283, this indicates that learning quality has an influence of 18.283 times greater on student academic achievement. Then the Odds ratio value of social support (X3) is 3.061, this shows that the effect of social support on student academic achievement is 3.061 times greater than if there is no social support. Meanwhile, variable (X2), namely time management, has no influence on student academic achievement. This is caused by students who do not have self-management skills or the ability to manage time. The implications of learning quality can be seen from students' understanding of the material presented, honing the courage to express opinions, increasing confidence in answering or asking questions and mental readiness and competence. The implication of social support is to reduce student stress and psychological pressure that can affect their academic performance.